The dynamics of mathematics classes with the use of games for teaching and learning natural numbers in basic education (Research, Society and Development, 2023)
The article in question brings the results of a participant research carried out in 2018 with students of the 3rd year of Elementary School in schools in the city of São Luís/MA with the initial use of bibliographical research, with the objective of demonstrating that the pedagogical practices in the teaching of Mathematics can be streamlined with the use of mathematical games, such as Asmd and Hexmultiplicative, in addition to showing that the game can be used as a didactic strategy within the teaching of Mathematics in order to streamline Mathematics classes. Questions such as: Can the pedagogical practices of mathematics be streamlined through pedagogical games, taking it from the level of an unpleasant subject? Thus, after applying the games and observing the students, we came to the conclusion of the importance that these activities had in the students' teaching-learning process in terms of attenuating the content and its activities in a fun and dynamic way.